Parameters of Body Composition Predict Clinical Course in Acute Colonic Diverticulitis - Surov, Alexey; Hinnerichs, Mattes; Shahzadi, Iram; Haag, Nina P.; Kröger, Jan Robert; Gerdes, Berthold; Elhabash, Saleem; Borggrefe, Jan (Journal of cachexia, sarcopenia and muscle, 2025)
ABSTRACT Background Acute colonic diverticulitis (ACD) is the most common complication of colonic diverticulosis. Body composition, that is, proportion, distribution and quality of muscle and adipose tissues may play a relevant role in ACD. Previously, only few reports with small number of patients analysed the prognostic role of body composition in ACD. Our purpose was to analyse associations between the occurrence of complications and parameters of body composition in patients with ACD in a large sample. Methods This retrospective study included 646 patients with ACD. The duration of hospital stay (days) and occurrence of complications were recorded. Parameters of body composition were semiautomatically measured with the freely available ImageJ software. Skeletal muscle area (SMA), skeletal muscle density, visceral adipose tissue (VAT), subcutaneous adipose tissue and intramuscular adipose tissue were estimated. To assess the impact of body composition parameters on ACD complications, Cox regression model (adjusted for sex and age) was used. Results Low skeletal muscle area (sarcopenia) was found in 322 patients (49.8%). High VAT was observed in 525 patients (81.3%). Low skeletal muscle density or myosteatosis was identified in 322 patients (49.8%). Length of hospital stay was prolonged in patients with sarcopenia, myosteatosis and/or visceral adiposity. Sarcopenia was an independent predictor for occurrence of complicated ACD, OR = 1.48, 95% CI (1.03–2.13), p = 0.033. Myosteatosis predicted occurrence of free perforation, OR = 2.36, 95% CI (1.01–5.43), p = 0.033. Furthermore, visceral adiposity tended to be a strong predictor of free perforation, OR = 7.62, 95% CI (1.29–138.00), p = 0.05. Finally, sarcopenia predicted occurrence of macro abscesses, OR = 2.41, 95% CI (1.41–4.26), p = 0.002. Conclusions Patients with sarcopenia, myosteatosis and visceral adiposity have prolonged length of hospital stay. Macro abscesses occur more frequently in patients with sarcopenia. Myosteatosis and high VAT are associated with free perforation.